2022
DOI: 10.21203/rs.3.rs-1359473/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and Practice of Breast Self Examination for Early Detection of Breast Cancer Among Young Women Attending Maternal Health Clinic at JOOTRH, Kisumu County

Abstract: Background Breast self-examination (BSE) is a simple, low-cost, and non-invasive method that women use to detect breast cancer at early stages. BSE is recommended for teenage and adult women as it helps to detect unusual swelling and lumps. The early intervention reduces the spread of cancer cells and improves health outcomes. This study assessed the knowledge and practices of BSE for early detection of breast cancer among women attending maternal health clinic at Jaramogi Oginga Teaching and Referral Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Negussie et al (2015) shows that only %16.5 of women, who are from Ethiopia, heard about BSE [40]. Contrary to these studies, the study conducted in Kenya showed that almost all of the young women had heard of Bse [41]. These results may suggest that demographic differences contribute to the inconsistent findings regarding the age and education level of the participants.…”
Section: Discussionmentioning
confidence: 91%
“…Negussie et al (2015) shows that only %16.5 of women, who are from Ethiopia, heard about BSE [40]. Contrary to these studies, the study conducted in Kenya showed that almost all of the young women had heard of Bse [41]. These results may suggest that demographic differences contribute to the inconsistent findings regarding the age and education level of the participants.…”
Section: Discussionmentioning
confidence: 91%